Political discourse and Islam: the role of rhetoric in Turkey - Shukri, Syaza Farhana Mohamad; Hossain, Ishtiaq (Bangladesh Institute of Islamic Thought, 2017)
Adaletve Kalkinma Partisi (AKP, Justice and Development Party) in Turkey has been blamed for Islamizing the Turkish society through its conservative policies that have similarity with discourses originating from the Islamic principles. However, the AKP government has maintained that it abides by Turkish laicism. This paper identifies and analyses the extent to which rhetoric by AKP’s leaders has changed over the years. This is done in order to find out whether the party truly has an intention to Islamize Turkey as part of a strategy to win votes. The paper highlights how the changes observed are related to the current national mood and issues being discussed. As a result, the AKP cannot be said to be a party that had always intended to turn Turkey into a religious country. The rhetoric employed by the leadership in the last 13 years showed that the shifts in discourse were to manage the support it received by conservative Turks, rather than as an upfront to the secular establishment.